2008
DOI: 10.1542/peds.2008-0715f
|View full text |Cite
|
Sign up to set email alerts
|

Professional Education in Child Abuse and Neglect

Abstract: Physicians have reported feeling that they were not adequately trained to identify and report child abuse. This article reviews the current state of medical education and residency training and the needs of physicians in practice and proposes changes and additions that can be made to improve the ability and confidence of physicians who are faced with the responsibility of keeping children safe. Pediatrics 2008;122:S13-S17 A MONG OUR MANY responsibilities, physicians are sentinels for child maltreatment. Federa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 28 publications
0
39
0
2
Order By: Relevance
“…The presence of ED staff with the necessary knowledge, skills and attitudes is therefore a key component in the recognition of child abuse 8. Educational programmes have been designed to improve clinical performance by improving knowledge and skills and by changing attitudes 9.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of ED staff with the necessary knowledge, skills and attitudes is therefore a key component in the recognition of child abuse 8. Educational programmes have been designed to improve clinical performance by improving knowledge and skills and by changing attitudes 9.…”
Section: Introductionmentioning
confidence: 99%
“…Barrier: No standards specify the quantity or quality of education that medical students, pediatric residents, or other physicians should receive about child maltreatment. 2 Many physicians indicate that they feel inadequately trained to identify and manage child maltreatment.…”
Section: Resultsmentioning
confidence: 99%
“…(Indeed, it was apparent that the interviewees themselves, who were sampled specifically because of their familiarity with the reporting regime, exhibited a shaky grasp of some of its details.) Studies of other mandatory reporting regimes have also found that mandated reporters often do not have the required training to properly fulfil their role 20. A fundamental tenet of the rule of law is that a law must be reasonably intelligible, clear and predictable for those to whom it applies 21.…”
Section: Discussionmentioning
confidence: 99%